A single pathological grading system for breast carcinoma should be adopted in Bangladesh - Sultana, Tuhin; Chowdhury, Abdul Allam; Rahman, Quddusur; Ahmed, AN Nashimuddin; Rahman, AJE Nahar (Bangladesh Journal of Pathology, 2010)
DOI: 10.3329/bjpath.v24i2.4112 Bangladesh J Pathol 24(2): 11-14